Adaptation and validation of academic resilience scale in Bengali - Ahmed, Riya; Panda, Bijoy Krishna; Sinha, Muktipada (Institute of Advanced Engineering and Science, 2025)
The purpose of the current study was to adapt and validate the Academic Resilience Scale (ARS-30) in the context of West Bengal and other Bengali-speaking regions. The research included a total of 628 participants. The data analysis occurred in three stages. Initially, confirmatory factor analysis was employed to assess the factorial validity of the Bengali version of ARS-30 scale, revealing a poor fit for the original three-factor model. Subsequently, further exploratory factor analysis (EFA) suggested a more suitable two-factor structure. In the third stage, this newly derived two-factor structure was validated through confirmatory factor analysis (CFA) with an independent sample. The adapted scale, renamed ARS-19, measures two factors related to academic resilience: negative affect and emotional response (6 items) and positive adaptation (13 items). Results from validity and reliability analyses indicated that the ARS-19 is a valid and reliable tool for assessing academic resilience in the aforementioned context. This study contributes to the literature by proposing a valid and reliable academic resilience measurement for West Bengal as well as other Bengali-speaking regions, facilitating practitioners in assessing academic resilience among higher education students.